The emerging role of DEAD/H-box helicases in hepatitis B virus infection - You, Hongjuan; Ma, Lihong; Wang, Xing; Zhang, Fulong; Han, Yiran; Yao, Jiaqi; Pan, Xiucheng; Zheng, Kuiyang; Kong, Fanyun; Tang, Renxian (Frontiers in Cellular and Infection Microbiology, 2022)
DEAD/H-box helicases are an essential protein family with a conserved motif containing unique amino acid sequences (Asp-Glu-Ala-Asp/His). Current evidence indicates that DEAD/H-box helicases regulate RNA metabolism and innate immune responses. In recent years, DEAD/H-box helicases have been reported to participate in the development of a variety of diseases, including hepatitis B virus (HBV) infection, which is a significant risk factor for hepatic fibrosis, cirrhosis, and liver cancer. Furthermore, emerging evidence suggests that different DEAD/H-box helicases play vital roles in the regulation of viral replication, based on the interaction of DEAD/H-box helicases with HBV and the modulation of innate signaling pathways mediated by DEAD/H-box helicases. Besides these, HBV can alter the expression and activity of DEAD/H-box helicases to facilitate its biosynthesis. More importantly, current investigation suggests that targeting DEAD/H-box helicases with appropriate compounds is an attractive treatment strategy for the virus infection. In this review, we delineate recent advances in molecular mechanisms relevant to the interplay of DEAD/H-box helicase and HBV and the potential of targeting DEAD/H-box helicase to eliminate HBV infection.